Custo da legalidade na extração madeireira no estado de Mato Grosso: implantação de manejos florestais - Alessandra Maria Filippin dos Passos; Wylmor Constantino Tives Dalfovo; Michele Jackeline Andressa Rosa (Confins)
Legalized forest management is an alternative for forest extraction, promoting social and social benefits in a sustainable way for a region where they are located. Increase in the remuneration for the implementation of forest management in the State of Mato Grosso. The following data were used: Internal Rate of Return (NPV), Internal Rate of Return (IRR), PAYBACK, and a detailed costing (fixed and variable). The research was done a field research and bibliographic review, based on the results obtained, from sources of forest management. The results showed that the costs of implanting a forest crop with a surface area of ​​917.88 hectares in Mato Grosso represent 6.95% of the total revenues from the commercialization of wood, with costs estimated at R $ 1,257. 974.47 and revenues in the amount of R $ 18,091,564.41. During the 30 years of the UPA, the value was R $ 603.052,15, making it necessary a little more than 2 (two) years for the actions to be equal to the costs deployment demonstrating that the forest management is a charitable and profitable the same data that may be a forest of deforestation and extraction illegal. The results of the financial indicators showed that the IRR was 48%, this rate is high during the economic literature. Regarding NPV, considering the cash flows at a rate of 10%, the amount of R $ 4,392,413.52 is considered positive in relation to the investment.